Therapeutic strategies after coronary stenting in chronically anticoagulated patients: the MUSICA study. Issue 18 (17th May 2009) - Sambola, A; Ferreira-González, I; Angel, J; Alfonso, F; Maristany, J; Rodríguez, O; Bueno, H; López-Minguez, J R; Zueco, J; Fernández-Avilés, F; Román, A San; Prendergast, B; et al.
Abstract : Objectives: To identify the therapeutic regimens used at discharge in patients receiving oral anticoagulant therapy (OAT) who undergo stenting percutaneous coronary intervention and stent implantation (PCI-S), and to assess the safety and efficacy associated with different therapeutic regimens according to thromboembolic risk. Design: A prospective multicentre registry. Setting: In hospital, after discharge and follow-up by telephone call. Patients and methods: 405 patients (328 male/77 female; mean (SD) age 71 (9) years) receiving OAT who underwent PCI-S between November 2003 and June 2006 from nine catheterisation laboratories of tertiary care teaching hospitals in Spain and one in the United Kingdom were included. Results: Three therapeutic regimens were identified at discharge: triple therapy (TT)—that is, any anticoagulant (AC) plus double antiplatelet therapy (DAT; 278 patients (68.6%); AC and a single antiplatelet (AC+AT; 46 (11.4%)) and DAT only (81 (20%)). At 6 months, patients receiving TT showed the greatest rate of bleeding events. No patients receiving DAT at low thromboembolic risk presented a bleeding event (14.8% receiving TT, 11.8% receiving AC+AT and 0% receiving DAT, p = 0.033) or cardiovascular event (6.7% receiving TT, 0% receiving AC+AT and 0% receiving DAT, p = 0.126). The combination of AC+AT showed the worst rate of adverse events in the whole cohort, especially in patients at moderate–high thromboembolic risk. Conclusions: In patients receiving OAT, TT was the most commonly used regimen after PCI-S. DAT was associated with the lowest rate of bleeding events and a similar efficacy to TT in patients at low thromboembolic risk. TT should probably be restricted to patients at moderate–high thromboembolic risk.